SUBPRIME MORTGAGE CRISIS IN THE UNITED STATES IN 2007–2008: CAUSES AND CONSEQUENCES (PART I) - Pajarskas, Vaidotas; Jočienė, Aldona (Ekonomika, 2015)
The main purpose of this article is to determine which factors and how contributed to the subprime mortgage crisis in the United States in 2007–2008, what their causal links and effects on the markets and the whole economy were, and to assess what actions could have been taken by the Federal Reserve and the Government in order to mitigate or prevent the consequences of subprime mortgage crisis and housing bubble. In order to obtain the research results, the authors performed a qualitative analysis of the scientific literature on the course of events and their development that led to the subprime mortgage crisis, and focused on the insufficiently regulated home mortgage market expansion, the impact on the subprime mortgage crisis of financial innovations and financial engineering, poorly evaluated systemic risks and policy undertaken by both the U.S. Government and the Federal Reserve before and after the crisis. The quantitative research focused on two main parts: firstly, analysis of the dependence between the causes of subprime mortgage crisis and the consequences, using a statistical and regression analysis, and secondly, an alternative path the Government and the Federal Reserve could have taken in their policy actions and the results they could have produced. The authors believe that the results of the research could give useful guidelines to the central bankers and government officials on how to make long-term decisions that can help in preparing for the financial distress, mitigating the consequences when the crisis strikes, accelerating the recovery and even preventing the crisis it in the future. The second part of the qualitative research will appear in the next issue of the journal.